Renal Function, Albuminuria, and the Risk of Cardiovascular Events After Kidney Transplantation - Lam, Ngan N. (Transplant Direct, 2018)
BACKGROUND: The risk of mortality and graft loss is higher in kidney transplant recipients with reduced estimated glomerular filtration rate (eGFR) and albuminuria. It is unclear whether these markers are also associated with cardiovascular events. METHODS: We examined linked healthcare databases in Alberta, Canada to identify kidney transplant recipients between 2002 and 2013 who had at least 1 outpatient serum creatinine and albuminuria measurement at 1-year posttransplant. We determined the relationship between categories of eGFR and albuminuria and the risk of subsequent cardiovascular events. RESULTS: Among 1069 eligible kidney transplant recipients, the median age was 52 years, 37% were female, and 52% had eGFR ≥60 mL/min per 1.73 m(2). Over a median follow-up of 6 years, the adjusted rate of all-cause mortality and cardiovascular events was 2.7-fold higher for recipients with eGFR 15-29 mL/min per 1.73 m(2) and heavy albuminuria compared to recipients with eGFR ≥60 mL/min per 1.73 m(2) and normal albuminuria (rate ratio, 2.7; 95% confidence interval, 1.3-5.7). Similarly, recipients with heavy albuminuria had a threefold increased risk of all-cause mortality and heart failure compared with recipients with eGFR ≥60 mL/min per 1.73 m(2) and normal albuminuria. CONCLUSIONS: These findings suggest that eGFR and albuminuria should be used together to determine the risk of cardiovascular outcomes in transplant recipients.